TRANSLATION QUALITY OF LITERARY TEXT OF INDONESIAN NOVEL “LASKAR PELANGI (THE RAINBOW TROOPS)” INTO ENGLISH USING FACEBOOK MACHINE TRANSLATION - Yeni Yulianti; Baharuddin; Lalu Jaswadi Putera; Udin (STKIP Subang, 2024)
This study aims to identify and categorize the types of corrections or post-edits found in English translations of Indonesian literary texts and evaluate the quality of these translations using Facebook Machine Translation (FMT), specifically in translating the Indonesian novel